(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The study aims to provide scientific evidence on the current status of patients’ compliance with Methadone treatment, proposing a plan to implement several measures to improve treatment effectiveness and limit drug re-use by patients at Kim Thanh Methadone Treatment Facility in 2023. Methods: Cross-sectional descriptive study on 86 patients being treated at Kim Thanh Methadone Facility with a treatment period of 3 months or more. Treatment compliance was assessed according to Decision No. 3140/QD-BYT dated August 30, 2010. Results: The rate of patients complying with treatment was 76.7%. The main reasons for patients skipping doses were being busy with work (57.1%), forgetting (14.2%), being sick (11.9%), not having enough money (9.5%), difficulty in traveling (4.8%), and other reasons accounted for 2.4%. During treatment, patients received support mainly from family members (97.7%) and medical staff (90.7%). Conclusion: The rate of patient compliance with treatment is 76.7%. To comply with treatment well, patients need support from many sides, the most important of which is the support of family members and medical staff.